Effects of a school-based ACT program on motivation, physical activity participation, motor competence, and physical performance in physically inactive female adolescent students - Hassan Gharayagh Zandi; Fatemeh Shaabani; Azam Noferesti; Elaheh Arab Ameri (PLoS ONE, 2026)
Adolescents face internal barriers like low self-confidence and psychological discomfort that limit physical activity. Adolescence offers a key window to enhance intrinsic motivation. Acceptance and Commitment Therapy (ACT) may effectively improve physical activity and motor competence through psychological flexibility and value-based behavior. This study examined the effects of an ACT-based intervention on physical activity participation, motivation, motor competence, and physical fitness in physically inactive adolescent girls. A randomized controlled trial involved 132 inactive girls aged 13–18, randomly assigned to either an ACT intervention or a control group. Intervention included seven sessions targeting six core ACT processes. Pre-and post-intervention assessments used standardized questionnaires and tests for physical activity participation, motivation, physical activity, motor competence, and fitness. ACT group showed significant improvements in intrinsic motivation, identified regulation, autonomy, and reduced amotivation and external regulation (p ≤ 0.05). Introjected regulation did not show a significant change (p > 0.05). Physical activity participation and fitness performance also improved significantly, along with both perceived and actual motor competence (p ≤ 0.05). ACT-based intervention effectively enhanced motivation, physical activity engagement, motor competence, and fitness. These findings support integrating ACT into school or community programs to promote sustainable physical activity habits in adolescent girls.